Type 2 Diabetes Mellitus and the Risk of Hepatitis C Virus Infection: A systematic review - Xuan Guo; Min Jin; Ming Yang; Ke Liu; Jùnwén Lǐ (2013)
Abstract The aim of this study was to evaluate the relationship between type 2 diabetes mellitus (T2DM) and hepatitis C virus (HCV) infection and to examine whether T2DM enhances the risk of HCV infection compared with the risk in the general population. We followed standard guidelines to perform a meta-analysis. The associated literature was selected based on the established inclusion criteria. The summary odds ratio (OR) and 95% confidence interval (95% CI) were used to investigate the strength of the association. Through electronic database and manual searching, 22 studies were identified for the final analysis, which included a total of 78,051 individuals. Based on the random effects model, the meta-analysis results showed that patients with T2DM were at a higher risk of acquiring HCV infection than non-T2DM patients (summary OR = 3.50, 95% CI = 2.54–4.82, I 2 = 82.3%). Based on the current limited evidence, this study suggests that T2DM is associated with increased susceptibility to HCV infection.